A Danish register‐based study on involuntary treatment in anorexia nervosa. Issue 11 (10th November 2018) - Clausen, L.; Larsen, J. T.; Bulik, C. M.; Petersen, L.
Abstract: Objective: Involuntary treatment is controversial and widely debated, but remains a significant component of treatment for severe anorexia nervosa. Given how little is known about this topic, we describe the frequency of various involuntary measures in a national cohort of all patients diagnosed with anorexia nervosa. In a subsample of patients, we explored predictors of the first involuntary measure recorded. Method: Descriptive statistics and Cox proportional hazard analyses were conducted using the national registers of Denmark covering the total population. Data from the National Patient Register and the Psychiatric Central Research Register including all psychiatric visits from 1969 onwards were merged with data from the National Register on Coercion covering 1999 onward. Involuntary measures registered between 2000 and 2013 were analyzed. Results: A total of 4, 727 patients with a diagnosis of anorexia nervosa representing 16, 592 admissions were included. Eighteen percent experienced at least one involuntary measure. A variety of measures were used with tube feeding being the most frequent followed by mechanical restraint, involuntary medication, physical restraint, constant observation, and sedative medication. A subsample of 2% of AN patients had more than 100 involuntary measures recorded. The first recorded involuntary measure was predicted by most but not all psychiatric comorbidities, especially schizophrenia, autism spectrum, and personality disorders, older age at first diagnosis, and previous admissions. Discussion: It is important to develop a more granular understanding of patients at risk of requiring involuntary treatment and to determine how best to treat them effectively with minimal use of involuntary measures.